THE SURGERY OF THE FUTURE IS HERE: CAPABILITIES OF THE DA VINCI SURGICAL SYSTEM (World Bulletin of Social Sciences, 2026)
This article examines the development of modern surgery, focusing on the implementation of the robotic Da Vinci Surgical System. Its key advantages are highlighted: high precision, minimal invasiveness, reduced complications, and accelerated patient recovery. The operating principles of the technology and prospects for its further development, including the integration of artificial intelligence, are briefly described. A conclusion is drawn regarding the significant role of robotic surgery in shaping the medicine of the future